Goal modelling for strategic dependency analysis in destination management - Garyfallos Fragidis; Iordanis Kotzaivazoglou (Journal of Tourism, Heritage & Services Marketing, 2022)
Purpose: The paper suggests goal modelling as a method for the strategic analysis in tourism destinations. Destination management is quite complex and challenging and requires deep understanding of the intentions, the roles and the strategies of the various stakeholders. Methods: This paper identifies the challenges and major issues of destination management, evaluates the capacity of goal modelling to address them and demonstrates the use of goal modelling for stakeholder and strategic analysis. Results: The paper provides a holistic, multi-level modelling approach that begins with stakeholder analysis, continues with the analysis of strategic dependencies between stakeholders and ends with the analysis of the strategic alignment of the Destination Management Systems. Goal modelling is used for the analysis of the roles and functions of stakeholders, the analysis of the interdependencies between stakeholders in terms of goals, tasks and resources, the selection between alternative business configurations, and the business model and strategic analysis. Implications: Three important issues of destination management are addressed: stakeholder analysis, strategic dependency analysis, and strategic alignment of information systems. The formalism of goal modelling can provide rigor and visualization in the analysis of the complex relationships in destination management.
Keywords: L1; L8; M1; 330; Destination management; destination management systems; strategic dependencies; stakeholder analysis